(untitled) - Stallings, William (Boston, 2014)
Includes bibliographical references and index; Data Communications, Data Networking, and the Internet -- Protocol Architecture, TCP/IP, and Internet-Based Applications -- Data Transmission -- Transmission Media -- Signal Encoding Techniques -- Digital Data Communication Techniques -- Data Link Control Protocols -- Multiplexing -- Spread Spectrum -- Circuit Switching and Packet Switching Asynchronous Transfer Mode -- Routing in Switched Networks -- Congestion Control in Data Networks -- Cellular Wireless Networks -- Local Area Network Overview -- Ethernet -- Wireless LANs -- Internetwork Protocols -- Internetwork Operation -- Internet Quality of Service -- Multiprotocol Label Switching -- Transport Protocols -- Computer and Network Security Threats -- Electronic Mail and Network Management -- Internet Directory Service and World Wide Web -- Sockets: A Programmer's Introduction -- Frame Relay
Keywords: Data transmission systems; Computer networks; Hệ thống truyền dữ liệu; Mạng máy tính